Identification of substances by paper and thin-layer chromatography : proceedings - International Symposium on Identification of Substances by Paper and Thin-Layer Chromatography (4th : 1969 : Frascati, Rome); Hais, I. M.; Lederer, Michael, 1924-; Macek, Karel (Amsterdam : Elsevier Pub., 1970)
42